Actor-network, conflict and the commodification of planning: Role of traditional food markets in shaping the built environment (2020)
This paper examines the processes of transformation of the architecture and spatial character of a Nigerian city, in (he planning and delivery of a sustainable built environment. It examines the intei dependency ot relationship between the traditional market space and the city which is constantly being challenged, adapted and simultaneously undermined by the city’s rapid growth and modernisation. Therefore, the meanings attached to the market and its built environment has not only changed on several levels front tire symbolic, sacred, religious use to commercial and mundane one but also has taken on new spatial forms in sustaining the life of the city due to the activities of tire various actors which is predicated on their worldview. Tire paper provides a detailed examination of the geographical location of the old mar ket built environment, in r elation to the expansion of the city over tittte. It traces historical changes hr the surrounding urban scape of the market, in particular, the location of developments, marry originating front tire colonial period, and their httpact on tire life of tire marker over time. It relates, how these historical relationships are registered both topographically and spatially providing supporting visual material such as maps and developmental plans. This paper fur ther expatiates on the understanding of negotiation and conflict that ensued during the inter action within the material environment of the city through the pr ism of the role of actors (government officials, users, planners, politicians) involved with the built marketplace in the snrdy area. Analyses provided through interpretive anthropology which is synchronic in nature (focus at events in a slice of rime) and those provided by Actor Network Theory (ANT) that is diachronic (focus on dynamic events through tune), i.e. anthropology focuses more ort the “static" past whereas ANT focuses on the activities of the actants in “dynamic" or "real-time". The paper concludes that theoretical and cultural interpretation impacts the physical mar ketplace, its form, character, and spatiality; this must itself be understood as an agent or actant in the struggle, in as much as it both enables and constrains human activities.